2017
DOI: 10.1155/2017/3037876
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Reverses the Diazepam‐Induced Cognitive Impairment by Modulation of Oxidative Stress and ERK 1/2/NF‐κB Pathway in Brain

Abstract: Oxidative stress and inflammation can be involved in cognitive dysfunction associated with neurodegenerative disorders. Diazepam (DZP) administration has been chosen to simulate the memory impairment. The aim of this study was to evaluate the effects of curcumin (CUR) on spatial cognition, ambulatory activity, and blood and brain oxidative stress levels. The ERK/NF-κB signaling pathway and the histopathological changes in the hippocampus and frontal lobe, in diazepam-treated rats, were also analyzed. The anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Curcumin longa, commonly referred as turmeric, is used widespread as an essential spice in food preparations mainly due to its medicinal properties. Curcumin exhibits a number of medicinal properties including anti-diabetic [1], anti-arthritic [2], anti-oxidant [3], anti-inflammatory [4], antimicrobial [5], anti-neurodegenerative [6]and anticancer [7]. Despite the widespread applications, the beneficial effects of curcumin are hampered by its poor bioavailability which results from its high metabolic and excretion rates, poor absorption and minimal water insolubility [8].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin longa, commonly referred as turmeric, is used widespread as an essential spice in food preparations mainly due to its medicinal properties. Curcumin exhibits a number of medicinal properties including anti-diabetic [1], anti-arthritic [2], anti-oxidant [3], anti-inflammatory [4], antimicrobial [5], anti-neurodegenerative [6]and anticancer [7]. Despite the widespread applications, the beneficial effects of curcumin are hampered by its poor bioavailability which results from its high metabolic and excretion rates, poor absorption and minimal water insolubility [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences have confirmed that DM is a major pathogenesis factor for cognitive deficits . Curcumin has been shown to be an effective agent for attenuating diabetic encephalopathy and improving surgery‐induced cognitive dysfunction in mice . In this study, we first explored the effects of the curcumin derivative NC on learning and memory performances of rats with DM induced by STZ.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,26 Curcumin has been shown to be an effective agent for attenuating diabetic encephalopathy and improving surgery-induced cognitive dysfunction in mice . 17,18,27 In this study, we first explored the effects of the curcumin derivative NC on learning and memory performances of rats with DM induced by STZ. Our results revealed that the declined cognitive functions in DM rats were significantly reserved by NC treatment, as evidenced by decreases in escape latency as well as increases in times across target quadrant in MWM test, and elevated DI in the novel object recognition test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have suggested that curcumin might be a potential therapeutic agent for preventing protein aggregation in Alzheimer's, and Parkinson's diseases [40]. Recent in vitro and in vivo investigations of curcumin's activities in neurodegenerative disease models [41][42][43][44][45][46][47][48][49][50] are summarized in Table 2. [47].…”
Section: In Vitro and In Vivo Studies Of Curcumin Properties In Neuromentioning
confidence: 99%